2007
DOI: 10.1016/j.contraception.2007.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Antiprogestin-releasing intrauterine devices: a novel approach to endometrial contraception

Abstract: Intrauterine devices (IUDs) that release progestins are highly effective contraceptives, but they induce breakthrough bleeding that some women find unacceptable. Because progesterone (P) antagonists (AP) are known to suppress the endometrium, induce amenorrhea, and inhibit fertility, AP IUDs may provide an effective contraceptive that also controls endometrial bleeding. Here we assessed the effects of empty (blank) vs AP-releasing (ZK 230 211) IUDs on bleeding patterns and endometrial growth in ovariectomized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
3
17
0
2
Order By: Relevance
“…Some studies have suggested that SPRMs may be able to control uterine bleeding via a direct effect on endometrial blood vessels (45,72,108,109), as amenorrhea in patients receiving SPRMs does not appear to depend on inhibition of ovulation in all cases (45,72). The mechanism of the amenorrhea observed after SPRM treatment is still poorly understood (110).…”
Section: Sprms For the Treatment Of Dysfunctional Uterine Bleedingmentioning
confidence: 96%
“…Some studies have suggested that SPRMs may be able to control uterine bleeding via a direct effect on endometrial blood vessels (45,72,108,109), as amenorrhea in patients receiving SPRMs does not appear to depend on inhibition of ovulation in all cases (45,72). The mechanism of the amenorrhea observed after SPRM treatment is still poorly understood (110).…”
Section: Sprms For the Treatment Of Dysfunctional Uterine Bleedingmentioning
confidence: 96%
“…Activation of mitogenactivated protein kinase has also been investigated [19,20]. In a therapeutic setting a new anti-progestin impregnated intrauterine device, showing to superior compared to the levonorgestrelimpregnated IUD in reducing breakthrough bleedings, also induced mucosal atrophy [21]. Mifepristone and other steroid receptor antagonists are assumed to be more potent than predicted by simple competition for progesterone binding and Mifepristone effectively antagonizes progesterone activation of the receptor at concentrations much less than sub-stoichiometric with the agonist [12].…”
Section: Introductionmentioning
confidence: 98%
“…Administration of the PRM ZK 230 211 using an intrauterine system (IUS) has been tested in primates 52 and in women 53 . The effects of a ZK 230 211-releasing IUS on bleeding patterns and endometrial growth in ovariectomized, artificially cycled macaques 52 has been compared to those of a blank device.…”
Section: New Routes Of Administration Of Prmsmentioning
confidence: 99%